Nestroft Validity for Screening of Extended Families of Thalassemia Patients - TAZEEN MAJEED, UMAR FAROOQ DAR, `MOHAMMED ADIL AKHTER, UJALA NAYYAR, (Journal of Fatima Jinnah Medical University, 2018)
Objective: To access effectiveness of NESTROFT as screening tool for detecting thalassaemia carriers in extended families of thalassaemia major /intermedia patients. Patients and Methods: In a cross sectional study total no. of 25 families of index cases of Thalassaemia, attending Thalassaemia unit of Fatma Jinnah Medical college, Lahore, Pakistan, were visited and 561 samples were collected for CBC, red cell indices, Naked-Eye-Single-Tube-Red-Cell-Osmotic-Fragility-Test (NESTROFT), Hb Electrophoresis and DNA analysis (if required),without prior iron administration. Average extended family size was 23.Thisstudy was conducted for duration of 15 months. Results: 515 NESTROFT tests were valid. 220 NESTROFT were positive and 295 NESTROFT were negative in detecting Thalassemia trait. Hb electrophoresis was performed as confirmatory test for Thalassemia trait. Sensitivity of NESTROFT was calculated as 55% and Specificity was 64%. Positive Predictive Value was 46% and Negative Predictive Value was 64%. Conclusion: NESTROFT may not be a good screening test for mass screening of iron deficient high risk population.